2019
DOI: 10.1016/j.abrep.2018.100154
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and impaired driving prevalence among Francophone and Anglophone postsecondary students in Western Canada

Abstract: Introduction Substance use and impaired driving increase risk of motor vehicle crashes and deaths. Individual, socio-economic and -cultural factors are associated with these at-risk behaviors; however, little is known if differences exist between the Anglophone majority and minority Francophone populations in Canada. This article describes prevalence of substance use, impaired driving and driving practices by postsecondary student and compares Francophones and Anglophones with respect to these beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Given such biases, heterogeneous reports are expected, and data must be interpreted with caution. For instance, in Manitoba, some reports suggest that addiction rates may be lower among French-speaking OLMC adults (although sometimes only marginally) compared with this province’s English-speaking majority (Chartier 28 ; Chartier et al, 29 ), while broader substance use may be greater among OLMC postsecondary student populations compared with their majority language peers (Gueye et al, 30,31 ). Others report substance-specific differences, with binge drinking being more prevalent among Anglophone (majority) and cannabis use more common among Francophone (OLMC) postsecondary students in this province 32 .…”
Section: Results and Key Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given such biases, heterogeneous reports are expected, and data must be interpreted with caution. For instance, in Manitoba, some reports suggest that addiction rates may be lower among French-speaking OLMC adults (although sometimes only marginally) compared with this province’s English-speaking majority (Chartier 28 ; Chartier et al, 29 ), while broader substance use may be greater among OLMC postsecondary student populations compared with their majority language peers (Gueye et al, 30,31 ). Others report substance-specific differences, with binge drinking being more prevalent among Anglophone (majority) and cannabis use more common among Francophone (OLMC) postsecondary students in this province 32 .…”
Section: Results and Key Findingsmentioning
confidence: 99%
“…Others report substance-specific differences, with binge drinking being more prevalent among Anglophone (majority) and cannabis use more common among Francophone (OLMC) postsecondary students in this province 32 . Also, rurality is reported to be a strong predictor of alcohol use for Manitoba’s OLMCs 30,33 . Furthermore, 1 study measured the impact of Canada’s 2018 recreational cannabis legislation on cannabis use among a postsecondary OLMC sample in Manitoba 34 .…”
Section: Results and Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that DG participation is common in many parts of the world and in light of the health risks associated with participating in this risky drinking activity, researchers in the U.S. (see Zamboanga et al, 2014; Zamboanga, Tomaso, et al, 2016) and other countries (e.g., Australia: Mulligan et al, 2016; Canada: Gueye et al, 2019; New Zealand: Bavin & Owens, 2016; Nigeria: Dumbili & Williams, 2017; United Kingdom: Moss et al, 2015; Netherlands: Hendriks et al, 2017) have paid attention to DG behaviors. Thus far, general alcohol intervention efforts have not been shown to be effective in reducing college attending emerging adults’ participation in DGs (Fernandez et al, 2017) or avoidance of DGs (Zamboanga, Merrill, et al, 2019) in the U.S. As such, there continues to be a need to further researchers’ and practitioners’ knowledge about DG behaviors and the extent to which DG participation is associated with an increased risk for heavy alcohol use and related health consequences among adolescents and emerging adults.…”
mentioning
confidence: 99%
“…Among university students in Australia (George & Zamboanga, 2018), 69% reported having played a DG at least once in the past 6 months while approximately 59% of adolescents and young adults in New Zealand indicated that they played DGs at least occasionally (Bavin & Owens, 2016). A study conducted with university students in Canada found that 51% played DGs in the past month most of the time or always (Gueye et al, 2019). Research indicates that those who play DGs report greater general alcohol consumption and are at increased risk for experiencing negative alcohol-related consequences (ARCs; for review, see Zamboanga et al, 2014).…”
mentioning
confidence: 99%